Towards the best employee performance model through sustainable management aspects - Simbolon, Netty Laura; Noermijati, Noermijati; Setiawan, Margono; Hapsari, Radhita Dwi Vata (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to examine and analyze the influence of work engagement and self-efficacy on employee performance, with the mediation of work behavior and perceived organizational support as moderation. The analysis used is statistical analysis in the form of SEM-PLS. The data collection method employs a survey method, with a research instrument in the form of a questionnaire. The population of this study consisted of civil servant employees of the Secretariat General of the Ministry of Manpower of the Republic of Indonesia, using a probability sampling technique with a total of 209 employees taken from a total population of 434. The results of the hypothesis test concluded that eight relationships between variables, mediation, and moderation were accepted, which strengthens the hypothesis built on the policy in the Ministry of Manpower in exploring the role of Social Cognitive Theory and Organizational Support Theory. Social Cognitive Theory (SCT) posits that perceived organizational support not only directly influences employee behavior but also shapes employee cognitive patterns. Employees begin to view themselves as competent and empowered individuals because organizational support reduces the fear of failure. Thus, the combination of perceived organizational support (OST) and self-efficacy (SCT) plays an important role in improving employee performance, encouraging innovation, and building a work culture that is responsive and adaptive to change. An interesting contribution of this study is the development of employee performance literature by proposing a conceptual model and framework to enhance work engagement and self-efficacy through perceptions of organizational support from the Indonesian Ministry of Manpower. This clarifies its role in enhancing human resource development, equipping individuals with essential skills and knowledge to achieve the SDGs, and building effective, accountable, and inclusive institutions at all levels.